Status of tuberculosis in bovine animals raised by tuberculosis infected patients in Western Chitwan, Nepal - Pandey, G; Dhakal, S; Sadaula, A; KC, G; Subedi, S; Pandey, KR; Dhakal, IP (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Bovine tuberculosis (bTB) is an important public health concern worldwide. This study was conducted to determine the status of bTB in animals raised by tuberculosis patients in Western Chitwan, Nepal. MATERIALS AND METHODS: This cross-sectional study was conducted from August, 2011 to January, 2012. A total of 100 bovines (cattle and buffalo) raised in 60 farms of tuberculosis patients were tested with single intradermal tuberculin test considering various animal factors. Well designed questionnaire survey was taken with 70 tuberculosis patients of same 60 families focusing knowledge, awareness and various practices related to bovine tuberculosis. RESULTS: Overall 15% bovines were positive for tuberculosis (13.6% cattle and 15.4% buffaloes). Age of animal was significantly associated with tuberculosis (p<0.05) while sex and species were not. 24% tuberculosis patients had raw milk consuming habit while very few of them (9%) were aware of zoonotic aspect of bovine tuberculosis. CONCLUSIONS: There is high chance of tuberculosis transmission form animals to humans or vice versa. Further detailed study is needed in large scale with stronger intersectoral collaboration of medical and veterinary health sector to determine the scale of problem and find out prevention and control strategies against zoonotic tuberculosis. DOI: http://dx.doi.org/10.3126/ijim.v1i2.7407 Int J Infect Microbiol 2012;1(1):49-53